Feminist solidarity building as embodied agonism: An ethnographic account of a protest movement. Issue 3 (12th February 2021) - Smolović Jones, Sanela; Winchester, Nik; Clarke, Caroline
Abstract : Feminist solidarity, after early and idealistic conceptions of an all‐encompassing sisterhood, has become preoccupied with understanding and theorizing differences between women. This study develops an account of solidarity as embodied agonism, where difference and contest are experienced and negotiated through the body. Difference and contest are reframed within feminist solidarity projects as resources for, rather than inhibitors to, generating collective agency. This is done through an ethnography of a protest movement in Montenegro, which drew together diverse groups of women, and bring our data into conversation with theories of agonistic democratic practice and embodied performativity. Embodied agonistic solidarity is theorized as a participative and inclusive endeavour driven by conflictual encounters, constituted through the bodies, language and visual imagery of assembling and articulating subjects. Our account of solidarity is presented as constituted through three dimensions, each of which represents a different emphasis on sensory experience: exposing, which is to make one's body open to the hardship of others, enabling alliances between unlikely allies to emerge; citing, which is to draw on others' symbolic resources and to publicly affirm them; inhabiting, which is to embody the deprivations of others, enabling alliances to grow and persist.